KEBIJAKAN HUKUM TERHADAP PELAKU PENYEBARAN IDENTITAS ANAK YANG BERHADAPAN DENGAN HUKUM DI MEDIA SOSIAL (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
As the most widely accessed type of internet content, the use of social media is currently being misused by irresponsible private account users (citizen journalism) which has led to the emergence of new crimes. One of them is the act of spreading the identity of children in conflict with the law (ABH) on social media either through the twitter, facebook, and instagram platforms. The examples of cases that the author took for this research are the case of the beating of a child victim of the Air Force in Pontianak, West Kalimantan and the case of the murder of a 15-year-old teenager (NF) against a toddler in Sawah Besar, Jakarta.The problem in this study is how the impact will occur on children if their identity is spread on social media and recognized by the public, and how are the regulations and sanctions for those who spread the identity of children who are in conflict with the law on social media. As it is known that the act of spreading the identity of children who are in conflict with the law violates the SPPA Law, the Child Protection Law, and the ITE Law, but in the law there are no rules regarding what sanctions can be imposed if someone violates these rules.Keywords: Impact – Regulation – Sanctions – Child Victims – Dissemination – Identity – Children in Conflict with the Law – Social Media